Origin assessment of EV olive oils by esterified sterols analysis. (1st December 2015) - Giacalone, Rosa; Giuliano, Salvatore; Gulotta, Eleonora; Monfreda, Maria; Presti, Giovanni
Highlights: EV olive oils Italian and non-Italian were differentiated by esterified sterols analysis. Our method meets origin requirements set out by Regulation Eu No. 29/2012. A noteworthy model was developed for prediction of origin of unknown samples. Esterified sterols show low correlation with ethylesters. Esterified sterols are promising in studies of geographical discrimination. Abstract: In this study extra virgin olive oils of Italian and non-Italian origin (from Spain, Tunisia and blends of EU origin) were differentiated by GC-FID analysis of sterols and esterified sterols followed by chemometric tools. PCA allowed to highlight the high significance of esterified sterols to characterise extra virgin olive oils in relation to their origin. SIMCA provided a sensitivity and specificity of 94.39% and 91.59% respectively; furthermore, an external set of 54 extra virgin olive oils bearing a designation of Italian origin on the labelling was tested by SIMCA. Prediction results were also compared with organoleptic assessment. Finally, the poor correlation found between ethylesters and esterified sterols allowed to hazard the guess, worthy of further investigations, that esterified sterols may prove to be promising in studies of geographical discrimination: indeed they appear to be independent of those factors causing the formation of ethyl esters and related to olive oil production.